Penguatan Profil Pelajar Pancasila dengan Mengintegrasikan Nilai-Nilai Multikultural - Muhamad Dawam Raihan; Arifin Maksum; Arita Marini (Cetta: Jurnal Ilmu Pendidikan, 2023)
Indonesia has a rich cultural heritage that is almost spread throughout the archipelago. The diversity that exists in Indonesia in terms of language, religion, customs, race makes Indonesia a multicultural country. Consequently, dynamics in culture such as assimilation, acculturation and diffusion will always be present during the plurality of the Indonesian people. Therefore, there is a need for the concept of multicultural education that can present cultural content in the learning process. One learning process that can integrate cultural content and shape student character is the Pancasila Student Profile Strengthening Project which is presented separately from intracurricular. The purpose of this study is to describe the implementation of the multicultural-based Pancasila Student Profile Strengthening Project (P5). The implementation of multicultural-based P5 is designed using multicultural concepts and approaches. This research is a qualitative type of research with descriptive methods. Data collection techniques were carried out by interview, observation and documentation. The research data was analysed interperatively and then described in a coherent manner based on the sequence of events in the P5 activities that have been carried out. The research was conducted at SDN Kramat 01 Central Jakarta from September to October 2023. The results showed that the implementation of P5 by integrating cultural content can be carried out optimally. The integration of diversity and richness of the nation's culture not only provides knowledge to students but fosters an attitude of tolerance, mutual respect and respect as well as preserving the culture that exists in Indonesia. The implementation of P5 by integrating cultural content needs to consider cultural content that is relevant and compile it into a comprehensive knowledge so that its application not only raises knowledge but also attitudes and skills in a multicultural society.